A Critique of the Book Named Professional Ethics in Education - Mohsen Rafi'i; Masoumeh Sharifi (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present study is to review, analyze, and criticize the book entitled “Professional Ethics in Education” written by Fātemeh Vejdāni. This book has been published with the purpose of providing an educational source for students-teachers at Farhangiyān University. The method of study is descriptive-analytic and the results showed that the book under study, in addition to its advantages and innovations, suffers from some disadvantages and drawbacks that were considered from two perspectives. The most noticeable drawbacks of the book include: 1) Structural and formal deficiencies: lack of correspondence between title of the book/table of contents and the approved syllabus, lacking a course book structure in writing, deficiency in giving references, lack of structural and conceptual relationship between educational objectives in some chapters, inconsistency between the summary of the chapters and their content, not observing necessary standards in "Questions for Contemplation", lack of balance in the arrangement of sections, chapters, and subchapters, and writing deficiencies; 2) Conceptual deficiencies: insistence on introductory and theoretical discussions in the first three chapters, little, inappropriate, and subjective use of religious genuine resources (The Noble Qur’an and the tradition of the infallible Imams), neglecting some arguments from the view of religious texts, mixing the history of creation and course of development with the background of research, repetitive quotations and lack of analysis, criticism, and precision, deficiency in the explanation of the concepts, concentration on the theoretical issues and negligence to presenting strategies and ethical skills of teaching. The results emphasize on the necessity of a serious consideration and rewriting of the book based on approved syllabi.